Biotechnology Learning through the Utilization of Natural Resources and Local Wisdom as a Foundation for Developing New Businesses in the Seulawah Valley Community of Aceh Besar - Almukarramah; Rubiah; Ibrahim; Jailani; Suryani; Ummul Mukminah (Jurnal Penelitian Pendidikan IPA, 2025)
The use of biotechnology, which relies on local natural resources and community wisdom, has enormous potential to advance the economy of rural communities, particularly in the Seulawah Valley, Aceh Besar. This study aims to explore how the biotechnology learning process can be optimized and implemented to support the sustainable development of new businesses. Using descriptive qualitative methods, this study investigates community understanding of biotechnology, the capacity of local resources, and the integration of local wisdom values in the development of biotechnology-based products. The results indicate that participatory learning methods in biotechnology encourage community creativity and innovation in processing agricultural, fishery, and medicinal plant products into products with high economic value, such as organic fertilizer and fermented foods. These findings emphasize the importance of integrating local knowledge and modern technology as a crucial foundation and basis for community-oriented economic development.